MANAJEMEN PENGELOLAAN DANA BAGI HASIL CUKAI HASIL TEMBAKAU DI KABUPATEN KUDUS - Ganda Nugraha; Susi Sulandari; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Kudus regency as one of the biggest cigarette’s tax producing in Indonesia. Based on that statement, so Kudus regency government arrange policy of governor’s rule No 4 2013 about guidelines for the management funds for tax results and tobacco’s result in Kudus regency. With the presence of its management, it is expected can help to decrease amount of destitution, unemployment, and increase economic development in Kudus Regency. The purpose of this study is to know how the system of management and how management of guidelines for the management funds for tax results and tobacco’s result in Kudus regency. Which to answer about the purpose and problems in this study is by using governor’s policy No 4 2013 as reference of management system and management theory by George R Terry in describing guidelines for the management funds for tax results and tobacco’s result in Kudus regency. The method used in this study is qualitative method by the study’s object are BAPPEDA, SEKDA and Dinas Perinkop and UMKM as SKPD of guidelines for the management funds for tax results and tobacco’s result in Kudus regency. The result of this study showed that in the implementation based on governor’s policy No 4 2013. In program that is funded by guidelines for the management funds for tax results and tobacco’s result both physical and non-physical give big effect to mid- low economy’s public in Kudus regency. In its implementation is still met problem, so that the result is far of the target. The problem is like limitedness of human resource in several SKPD. This case can be seen from the activity that is not spread all over yet in Kudus regency and the performance accomplishment that is not spread all over carried out yet.